In situ synthesis and microfabrication of high entropy alloy and oxide compounds by femtosecond laser direct writing under ambient conditions - Hegde, Chidanand (2022)
Synthesis and coating of multi-metal oxides (MMOs) and alloys on conductive substrates are indispensable to electrochemical applications, yet demand multiple, resource-intensive, and time-consuming processes. Herein, an alternative approach to the synthesis and coating of alloys and MMOs by femtosecond laser direct writing (FsLDW) is reported. A solution-based precursor ink is deposited and dried on the substrate and illuminated by a femtosecond laser. During the illumination, dried precursor ink is transformed to MMO/alloys and is simultaneously bonded to the substrate. The formulation of the alloy and MMO precursor ink for laser processing is universally applicable to a large family of oxides and alloys. The process is conducted at room temperature and in an open atmosphere. To demonstrate, a large family of 57 MMOs and alloys are synthesized from a group of 13 elements. As a proof of concept, Ni0.24 Co0.23 Cu0.24 Fe0.15 Cr0.14 high entropy alloy synthesized on stainless-steel foil by FsLDW is used for the oxygen evolution reaction, which achieves a current density of 10 mA cm-2 at a significantly low overpotential of 213 mV. Further, FsLDW can also achieve microfabrication of alloys/MMO with feature sizes down to 20 µm.